2001
DOI: 10.1093/intimm/13.9.1121
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic heat shock proteins as molecular links in innate and adaptive immune responses: Hsp60-mediated activation of cytotoxic T cells

Abstract: Heat shock proteins (HSP) like Hsp60, Hsp70 and gp96 act directly on antigen-presenting cells (APC), e.g. by inducing the secretion of cytokines. Here we analyzed the impact of Hsp60 on the antigen-specific activation of CD8(+) T cells in a TCR transgenic system. Hsp60 induced low amounts of IFN-gamma in the absence of antigenic peptide; however, the release of IFN-gamma is increased by a factor of 3-10 following the addition of Hsp60 to purified populations of OT-1 [ovalbumin (OVA)257-264/H2-K(b)-restricted] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 30 publications
0
35
1
Order By: Relevance
“…7). HSPs, while playing an important role in the stimulation of innate immunity through TLRs, also activates T cell and B cell lymphocytes Moré et al 2001); moreover, HSPs can directly activate the adaptive immune T lymphocytes in a TLR2-dependent and TLR4-independent manner, while Hsp60 activates B cells via TLR4 recruitment (Zanin-Zhorov et al 2003;Cohen-Sfady et al 2005;Osterloh et al 2008).…”
Section: Heat Stress Regulates Genes Involved In Immune Response and mentioning
confidence: 99%
“…7). HSPs, while playing an important role in the stimulation of innate immunity through TLRs, also activates T cell and B cell lymphocytes Moré et al 2001); moreover, HSPs can directly activate the adaptive immune T lymphocytes in a TLR2-dependent and TLR4-independent manner, while Hsp60 activates B cells via TLR4 recruitment (Zanin-Zhorov et al 2003;Cohen-Sfady et al 2005;Osterloh et al 2008).…”
Section: Heat Stress Regulates Genes Involved In Immune Response and mentioning
confidence: 99%
“…Nuclease protection assay was performed with a 71-mer oligonucleotide spanning the splice junction of soluble Fit-1S and membrane Fit-1M, which was 3Ј-end labeled with 32 Pdd[␣-ATP] (Amersham) using terminal deoxynucleotidyl transferase. Nuclease-digested hybridized products were electrophoresed through a 5% polyacrylamide gel followed by autoradiography.…”
Section: Rna Analysismentioning
confidence: 99%
“…In contrast to CD45RA+ RO-(naive) and CD45RA-RO+ (memory) cells, T cell populations proliferated after stimulation with bacterial Hsp60 from Mycobacterium leprae, Escherichia coli or Chlamydia trachomatis; (4) as human Hsp60 acts not only directly on antigen-presenting cells (APC) by inducing the secretion of cytokines but also on other leucocytes, the impact of Hsp60 on the antigen-specific activation of CD8 + T cells was studied. 20 It was found that Hsp60 enhances the activation of cytotoxic T cells through activated macrophages, thus acting as a molecular link between innate-and adaptativeimmune systems; (5) IL-12 was found to play a central role in Hsp60-mediated IFNg induction, which was dependent on costimulatory signals provided by B7-CD28 cells; 21 (6) peripheral blood lymphocytes (PBL) produced Th1-associated peripheral blood lymphocytes (PBL) produced Th1-associated cytokines, including IFNg and IL-12, spontaneously and in response to stimulation with exogenous HSP60-derived peptide; 22 (7) human Hsp60 acts as a costimulator of the human regulatory T cells (Tregs) CD4 + CD25 int and CD4 + CD25 hi ; 23 (8) Hsp60 inhibited IFNg and TNFa secretion and upregulated IL-10 secretion by activated CD4 + T cells. 23 Hsp60 could very well act as a costimulator of CD8+ lymphocytes, and Hsp60-treated CD4 + CD25 + T cells could regulate CD8 + T cell cytokine secretion.…”
Section: Introductionmentioning
confidence: 99%